Amazonian indigenous territories as reservoirs of biodiversity: The army ants of Santa Sofia (Amazonas – Colombia) - Catalina Sanabria; Rafael Achury (Caldasia)
The Amazon basin is undergoing processes of global change that threaten one of the planet’s greatest sources of biological and cultural richness. Among different conservation strategies, indigenous re-serves play a key role by reducing the impact of factors such as the deforestation caused by the expan-sion of the agricultural frontier. Despite the demonstrated importance of these indigenous territories, there is a lack of studies evaluating their contribution to the regional diversity in Colombia, especially for invertebrate groups. By surveying indigenous territories for the first time in the Amazonas depart-ment, we investigated the army ant fauna inhabiting different land use types: forests; “chagras” in different stages of regeneration; and pastures. In a sampling plot that represents just 0.0014 % of the department’s area, four genera and eight army ants species were recorded, representing 47 % of known species in the Amazonas department and 18 % in Colombia. Our sampling revealed three new records for the department and Neivamyrmex diana as a new record for the country. Mature forests harbored six species, while the chagras system retained up to five species. Notably, when placing our results in a national context, we revealed several country regions and departments (e.g., Córdoba, Sucre, Vaupés) that presented limited or no information on army ant diversity. Our results provide justification for the continuous evaluation, monitoring and conservation of indigenous reserves, based not only on their demonstrated cultural and ancestral importance but to their potential to retain high biodiversity.